Cell‐to‐cell cross‐talk between mesenchymal stem cells and cardiomyocytes in co‐culture - Plotnikov, E. Y.; Khryapenkova, T. G.; Vasileva, A. K.; Marey, M. V.; Galkina, S. I.; Isaev, N. K.; Sheval, E. V.; Polyakov, V. Y.; Sukhikh, G. T.; Zorov, D. B. (Journal of cellular and molecular medicine, 2008)
The goals of the study were: (1) to explore the communication between human mesenchymal stem cells (MSC) and rat cardiac myocytes resulting in differentiation of the stem cells and, (2) to evaluate the role of mitochondria in it. Light and fluorescence microscopy as well as scanning electron microscopy revealed that after co‐cultivation, cells formed intercellular contacts and transient exchange with cytosolic elements could be observed. The transport of cytosolic entity had no specific direction. Noticeably, mitochondria also could be transferred to the recipient cells in a unidirectional fashion (towards cardiomyocytes only). Transmission electron microscopy revealed significant variability in both the diameter of intercellular contacting tubes and their shape. Inside of these nanotubes mitochondria‐resembling structures were identified. Moreover, after co‐cultivation with cardiomyocytes, expression of human‐specific myosin was revealed in MSC. Thus, we speculate that: (1) transport of intracellular elements to MSC possibly can determine the direction of their differentiation and, (2) mitochondria may be involved in the mechanism of the stem cell differentiation. It looks plausible that mitochondrial transfer to recipient cardiomyocytes may be involved in the mechanism of failed myocardium repair after stem cells transplantation.